EU Membership: Implications for Czech Energy Security - Svec, Martin (Maastricht 30: A Central European Perspective, 2025)
This paper examines the evolution of the Czech Republic’s energy security from the 1990s, focusing on its political, economic, and infrastructural challenges. During this period, the country was heavily dependent on imports of both oil and natural gas from the USSR/Russian Federation, with an energy infrastructure primarily structured to facilitate these imports. The first section of the paper examines the steps taken by Czechoslovakia and, later, the Czech Republic to diversify its energy sources and infrastructure, as well as the country’s efforts to join international organizations, including the International Energy Agency. The second part analyses the evolution of the European Union’s energy security policy and its implications forCzech energy security in the context of its EU membership. The paper mentions the role of the Czech Republic during its Presidency of the Council of the European Union in 2022, illustrating how EU membership has been central to enhancing the nation’s energy resilience. Through EU solidarity and cooperation, the Czech Republic has strengthened its energy security, adapting to evolving challenges and crises. Keywords: EU Energy Law; Energy Law; Energy Security; Czech Republic; EU Membership